The impacts of EU cohesion policy on sustainable tourism: The case of POSEUR in Algarve - Valente, B.; Medeiros, E. (Sustainability, 2022)
Sustainable tourism is a main priority of European Union policies, with the aim of mitigating the potential harmful consequences of this sector on a given territory. The main research goal of this article is to better understand the impact of the public investments financed via EU Cohesion Policy in the tourism sector in the Portuguese Algarve NUT2. This paper focuses on the Portuguese Operational Programme for Sustainability and Efficient Use of Resources (POSEUR 20142020), which was an operational programme of a Portuguese framework to implement EU Cohesion Policy funds in Portugal between 2014 and 2020, and was specifically focused on supporting sustainable development processes. The sustainability performance of POSEUR in the Algarve was evaluated in five different dimensions of analysis: (1) low-emissions economy, (2) adaptation to climate change, (3) risk prevention and management, (4) environmental protection, and (5) resource efficiency. The results showed that POSEUR had a low impact in almost all dimensions in the Algarve, apart from the adaptation to climate change dimension, which exhibits a high impact score, mostly due to the support given for carrying out the Plans for Adaptation to Climate Change (PAAC).